Developing Islamic Sustainable and Responsible Investment Criteria: an Overview - Haji Wahab, Muhammad Zarunnaim; Mohamed Naim, Asmadi (Emerald Publishing Limited, 2023)
Purpose – The purpose of this study is to explore the necessity for developing Islamic sustainable and responsible investment (i-SRI) criteria based on environmental, social and governance issues. Design/methodology/approach – To address the above objective, this study adopted a qualitative method via content document analysis and interviews with experts.